Procedural and distributive justice: Effects on attitudes toward body-worn cameras - Mrozla, Thomas (International journal of police science & management, 2021)
The purpose of this study was twofold. First, it examined how procedural and distributive justice influence college students’ perceptions of adoption of body-worn cameras by the police. Second, it explored how procedural and distributive justice influence college students’ perceptions of the ability of body-worn cameras to improve community relations, decrease citizen complaints, increase police officer respect, increase citizen respect, and improve training. Those who perceived distributive injustice were more likely to agree that the police should adopt body-worn cameras. Perceived distributive injustice was also a consistent predictor regarding the varying abilities of body-worn cameras.